Pengaruh Kualitas Pelayanan dan Persepsi Harga terhadap Kepuasan Pelanggan Pengguna Jasa Go-Ride dalam Aplikasi Go-Jek di Kota Tasikmalaya : Survei pada Mahasiswa Prodi Manajemen Periode Tahun 2018 Universitas Perjuangan Tasikmalaya - Ema Nurulhuda (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of service quality and price perception on customer satisfaction of Go-Ride service users in the Go-Jek application in the City of Tasikmalaya (Survey of Management Study Program students for the 2018 period, Perjuangan University). This type of research is quantitative research with causality method and survey approach. The sample that will be selected in this study is the Student of Management Study Program for the Period of 2018 Universitas Struggle Tasikmalaya, as many as 80 people. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that Service Quality and Price Perception had a significant influence on customer satisfaction in Management Study Program students for the 2018 period. Partially, Service Quality has a significant influence on Customer Satisfaction in Management Study Program Students for the 2018 Period. Price Perception has a significant influence on Customer Satisfaction in Management Study Program Students for the 2018 Period at Perjuangan University.